Answer:
![f(x)=5x^(3)-65x-60](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yteq1st7iqfi65czefdi2hxhjcr2pwm2lc.png)
Explanation:
we know that
The roots are
x=-3,x=-4 and x=1
so
The equation of a polynomial of degree 3 with real coefficients and zeros of minus3,minus1, and 4 is equal to
![f(x)=a(x+3)(x+1)(x-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pzcqpk07vpt6mmdr6mp6iitcnqnfwrbo50.png)
Remember that
----> given value
For x=-2, f(x)=30
substitute and solve for the coefficient a
![30=a(-2+3)(-2+1)(-2-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z9kfc51wsadxng8mfborz6v5h4rlf8sv08.png)
![30=a(1)(-1)(-6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q2wzn345bx53ddgguap0ulbc897044kh6f.png)
![30=6a](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6089g02rm2t0z9gd3izhlv7v19spoto70m.png)
![a=5](https://img.qammunity.org/2020/formulas/mathematics/high-school/54fdweyb8wyeue10yov59os9w11gn85p3f.png)
so
The polynomial is
![f(x)=5(x+3)(x+1)(x-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/543rhde6ijsxeauux89fz78jq34wqp2it0.png)
Apply distributive property
![f(x)=5(x+3)(x+1)(x-4)\\f(x)=5(x+3)(x^(2)-4x+x-4)\\f(x)=5(x+3)(x^(2)-3x-4)\\f(x)=5(x^(3)-3x^(2)-4x+3x^(2)-9x-12)\\f(x)=5(x^(3)-13x-12)\\ f(x)=5x^(3)-65x-60](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cn5obmlbfu016xksxac829k331i8sc7keq.png)